Compositional engineering of the pi-conjugated small molecular VOPcPhO : Alq3 complex to boost humidity sensing. Issue 32 (4th April 2017) - Fatima, Noshin; Aziz, Fakhra; Ahmad, Zubair; Najeeb, M. A.; Azmeer, M. I.; Karimov, Kh. S.; Ahmed, M. M.; Basheer, S.; Shakoor, R. A.; Sulaiman, K.
Abstract : This study exhibits a solution-processed organic semiconductor humidity sensor based on vanadyl 2, 9, 16, 23-tetraphenoxy-29 H, 31 H -phthalocyanine (VOPcPhO), tris-(8-hydroxy-quinoline)aluminum (Alq3 ), and their composites. Abstract : This study exhibits a solution-processed organic semiconductor humidity sensor based on vanadyl 2, 9, 16, 23-tetraphenoxy-29 H, 31 H -phthalocyanine (VOPcPhO), tris-(8-hydroxy-quinoline)aluminum (Alq3 ), and their composites. Compositional engineering of the VOPcPhO : Alq3 complex was performed to develop a sensitive humidity sensor with a linear response. Thin films of VOPcPhO, Alq3, and composites were spin-coated over pre-deposited aluminum (Al) electrodes, whereas the other electrodes were deposited through a thermal evaporation technique. Both capacitive and resistive responses were measured as a function of different relative humidity levels. Morphological and structural properties of the organic thin films were characterized by atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), and Fourier transform infrared spectroscopy (FTIR). Compared to the VOPcPhO and Alq3 stand-alone sensors, the VOPcPhO : Alq3 composite-based sensor demonstrated superior performance with significantly improved sensing parameters, highlighting unique advantages of the low-molecular composite-based thin film organic humidity sensors.